Pengaruh Penggunaan Kontrasepsi Depo Provera terhadap Timbulnya Melasma di Puskesmas Ngoresan Surakarta - Tiffany, Firstiafina; Dewi, Yulia Lanti Retno; Setyawan, Sigit (Nexus Kedokteran Komunitas, 2013)
Background: One side effect of Depo Provera Contraceptive usage is the emergence of melasma on the face. Research about the influence of Depo Provera contraceptive usage on the incidence of melasma has never existed in Ngoresan Public Health Center Surakarta. Therefore, the authors are interested to know whether a speckling of hyperpigmentation / melasma on the face can be caused due to the usage of contraceptive Depo Provera. Methods: This study used analytic observational with a retrospective cohort study approach. This study was conducted in March-April of 2013. Subjects in this study were women aged 20-40 years in Ngoresan Public Health Center Surakarta. The sampling technique used was fixed exposure sampling to the sample size of 60 people. Data collection used questionnaires and direct observations. Then, data were analyzed using the chi square test at 95% confidence level (p > 0.05). Results: Based on the calculation, obtained p value = 0.010 < limit value of significance p = 0.05 level. So H0 is rejected and H1 is accepted. Means there is a significant effect on the Depo Provera contraceptive usage on the incidence of melasma on the face at the Ngoresan Public Health Center Surakarta. Conclusions: From the research it can be concluded that the obtained statistically significant results on the effect of Depo Provera contraceptive usage on the incidence of melasma on the face at the Public Health Center Ngoresan Surakarta. The longer the usage of contraceptive Depo Provera more likely arise melasma. Keywords: Depo Provera Contraception, Melasma Â